HUBUNGAN MINAT BELAJAR DENGAN HASIL BELAJAR IPS SISWA KELAS IV SDN SE-KECAMATAN KEBUMEN TAHUN AJARAN 2019/2020 - Diah Monitasari Monitasari; Suhartono Suhartono; Joharman Joharman (Universitas Sebelas Maret, 2020)
Interest in learning affects student learning outcomes in learning process. Lack of students’ interest in learning makes low social science learning outcomes. The study aimed to determine the positive correlation between students' interest in learning and social science learning outcomes and to determine the contribution of interest in learning to social science learning outcomes of fourth grade students of public elementary schools in Kebumen sub-district in academic year of 2019/2020. It was quantitative research design with correlation method. The sampling method used cluster random sampling technique. The result indicated that there was positive correlation between interest in learning and social science learning outcomes with low correlation level which was 0.245. The adjusted R square value of interest in learning to social science learning outcomes was 5.96%. It concludes that there is positive correlation between interest in learning and social science learning outcomes to fourth grade students of public elementary schools in Kebumen sub-district in academic year of 2019/2020.